The RNA Polymerase II Factor RPAP1 Is Critical for Mediator-Driven Transcription and Cell Identity - Cian J. Lynch; Raquel Bernad; Isabel Calvo; Sandrina Nóbrega-Pereira; Sergio Ruiz; Nuria Ibarz; Ana Martinez-Val; Osvaldo Graña-Castro; Gonzalo Gómez-López; Eduardo Andrés-León; Vladimir Espinosa Angarica; Antonio del Sol; et al. (Cell Reports, 2018)
Summary: The RNA polymerase II-associated protein 1 (RPAP1) is conserved across metazoa and required for stem cell differentiation in plants; however, very little is known about its mechanism of action or its role in mammalian cells. Here, we report that RPAP1 is essential for the expression of cell identity genes and for cell viability. Depletion of RPAP1 triggers cell de-differentiation, facilitates reprogramming toward pluripotency, and impairs differentiation. Mechanistically, we show that RPAP1 is essential for the interaction between RNA polymerase II (RNA Pol II) and Mediator, as well as for the recruitment of important regulators, such as the Mediator-specific RNA Pol II factor Gdown1 and the C-terminal domain (CTD) phosphatase RPAP2. In agreement, depletion of RPAP1 diminishes the loading of total and Ser5-phosphorylated RNA Pol II on many genes, with super-enhancer-driven genes among the most significantly downregulated. We conclude that Mediator/RPAP1/RNA Pol II is an ancient module, conserved from plants to mammals, critical for establishing and maintaining cell identity. : Lynch et al. report a regulator of RNA Pol II called RPAP1, displaying functional conservation from plants to mammals. RPAP1 is required to establish and maintain cell identity. Mechanistically, RPAP1 is critical for the Mediator-RNA Pol II interaction, thereby preserving normal transcription at enhancer-driven genes. Keywords: transcription, RNA polymerase II, Mediator, cell identity, differentiation, interactome, enhancer